2016
DOI: 10.1089/chi.2015.0109
|View full text |Cite
|
Sign up to set email alerts
|

Are Mealtime Best Practice Guidelines for Child Care Centers Associated with Energy, Vegetable, and Fruit Intake?

Abstract: Background: Mealtime best practices for obesity prevention in child care have been developed from experimental studies and expert opinion. Our objective was to describe adherence to best practices in child care centers and to evaluate the association between mealtime practices and children's dietary intake.Methods: We conducted an observational study of 349 preschoolers, ages 36 to 72 months, from 30 child care centers in Cincinnati, Ohio (November 2009 to January 2011). Trained observers recorded providers' b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 31 publications
3
50
0
Order By: Relevance
“…The energy and nutrients consumed were within acceptable distribution ranges for young children and similar to previous reports in the U.S., 25,39 , although lower than childcare centers abroad. 27 A previous report of American Indian preschoolers conducted over the full day reported the same fat consumptionbut higher carbohydrate and lower protein.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The energy and nutrients consumed were within acceptable distribution ranges for young children and similar to previous reports in the U.S., 25,39 , although lower than childcare centers abroad. 27 A previous report of American Indian preschoolers conducted over the full day reported the same fat consumptionbut higher carbohydrate and lower protein.…”
Section: Discussionsupporting
confidence: 87%
“…60 However, a high prevalence of centers participated in family-style meal service (36% vs. 8–12%). 25,36 Observations in this study are similar to self-reported practices. 29,61 Given the variation between self-report and researcher observations, it is likely that providers are aware of the best-practice recommendations 3,23 and may be attempting to implement family-style meal service, yet are not fully compliant.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Kharofa et al 35 propose a guide for such interventions with subsidize steps to guide appropriate practices at mealtime. Since family mealtime,is dependent of parental behavioral pattern and socioeconomic conditions, they become the main focus of the interventions and not the children.…”
Section: Impact On the Bmi And Food Qualitymentioning
confidence: 99%